Mental Health Conditions and Quality of Life among Online Gambling College Students: A Descriptive Study - Wulandari, Devi; Saputra, Dinar; Ardiansyah, Zaidan (Universitas Ahmad Dahlan, 2024)
The phenomenon of online gambling is widespread among college students in Indonesia. However, little is known about its impact on their mental health and health-related quality of life. This study aimed to examine the mental health and quality of life of college students affected by online gambling. A cross-sectional survey was conducted with online questionnaires distributed to 118 students who had engaged in online gambling within the past 12 months. The Self-Report Questionnaire-20 (SRQ-20) and the 12-Item Short FormHealth Survey (SF-12) were used for assessment. Results showed that Mental ComponentSummary (MCS-12) scores were lower than Physical Component Summary (PCS-12)scores. Respondents reported issues such as sleep disturbances, difficulty enjoying daily activities, fatigue, decision-making struggles, lack of a sense of purpose, feelings of unhappiness and worthlessness, nervousness, and frequent worry. These findings suggest that online gambling may have a harmful effect on students' mental health and overall quality of life.